Pengembangan Media Pembelajaran Interaktif Mengunakan Ispring Suite pada materi Software Kelas VIII SMP - Julius Kalangi; Dewi Rosita (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study uses the Research and Development (R&D) research type with the PPE model consisting of three stages, namely Planning, Production and Evaluation. The research subjects involved 35 students from class VIII (8) at SMP Samarinda as well as 3 media experts and 1 material expert. The object of the study was the Ispring Suite teaching material on Software material.The results of the study showed that the development of Ispring Suite which was tested by 3 expert media validators received a Calculation value of 172 which indicated the category of